Tracking Structural Phase Transitions in Lead-Halide Perovskites by Means of Thermal Expansion - Keshavarz, Masoumeh (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.